Utilization of quantitave methods in the decision making process of a manager - Duspiva, Pavel; Novotný, Josef (Univerzita Pardubice, 2010)
For economic phenomena and their quantification there is a range of models that produce varying results depending on their formulation. In relation to investment decision making various models for calculation of the intrinsic value per share and their differing results are demonstrated. In order to use individual models, market value forming factors, which are the basis of these models, are defined as well as assumptions for their validity.
Keywords: quantitative methods; maher; intrinsic value per share; models; decision making